2022
DOI: 10.1001/jamanetworkopen.2022.36751
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Mental Illness Risk Among North Korean Refugees and Immigrants Resettled in South Korea

Abstract: ImportanceThe global increase in the numbers of refugees and immigrants has made mental health a major public concern. Although they are divided, North and South Korea share a common ethnic heritage.ObjectiveTo investigate mental illness risk among North Korean immigrants living in South Korea and compare it with that of the general South Korean population.Design, Setting, and ParticipantsThis retrospective, population-based cohort study was based on National Health Insurance claims data from 2007 to 2019, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Both ordinary least squares (OLS) and quantile regression (QR) results reveal that PoD_mental and PoD_speech were signi cantly positively correlated with the migrant population, with coe cients increasing across quantile levels. This is in line with previous research (Tinghög, 2009; Pollard and Howard, 2021; Lee et al, 2022) suggesting that factors such as environmental stressors, language barriers, discrimination, and social isolation may lead to higher mental illness rates among migrants (Shah et al, 2019; Pollard and Howard, 2021). Migrants, who often have temporary residence and frequent relocation, may face higher speech disability risks than permanent residents.…”
Section: Migrant-dominated Typesupporting
confidence: 90%
“…Both ordinary least squares (OLS) and quantile regression (QR) results reveal that PoD_mental and PoD_speech were signi cantly positively correlated with the migrant population, with coe cients increasing across quantile levels. This is in line with previous research (Tinghög, 2009; Pollard and Howard, 2021; Lee et al, 2022) suggesting that factors such as environmental stressors, language barriers, discrimination, and social isolation may lead to higher mental illness rates among migrants (Shah et al, 2019; Pollard and Howard, 2021). Migrants, who often have temporary residence and frequent relocation, may face higher speech disability risks than permanent residents.…”
Section: Migrant-dominated Typesupporting
confidence: 90%
“… 4 A recent large-scale analysis that assessed over 22 000 NKDs with propensity score matching against 90 000 people in South Korea indicated that NKDs have higher risk of developing mental disorders than South Koreans, with a hazard ratio of 2.12. 5 Unsurprisingly, PTSD had the highest hazard ratio of 3.10, suggesting harmful effects of the traumatic experiences of displaced individuals, as emphasised in previous studies. 6 , 7 Difficulties in adapting to a new environment can be worsened by symptoms of PTSD in refugees.…”
mentioning
confidence: 63%
“…Although they still have the same ethnicity and language, differences in culture, ideology, government regulations and socioeconomic status have grown significantly, making it difficult for NKDs to adapt and settle in South Korea 4 . A recent large-scale analysis that assessed over 22 000 NKDs with propensity score matching against 90 000 people in South Korea indicated that NKDs have higher risk of developing mental disorders than South Koreans, with a hazard ratio of 2.12 5 . Unsurprisingly, PTSD had the highest hazard ratio of 3.10, suggesting harmful effects of the traumatic experiences of displaced individuals, as emphasised in previous studies 6 , 7 .…”
mentioning
confidence: 99%